Edukasi Gizi pada 8000 Hari Pertama Kehidupan sebagai Upaya Pencegahan Stunting melalui Permainan Edukatif Monopoly Nutriboard di Desa Harjomulyo - Fitriyah, Holif; Rachmawati, Septi Nur; Ervyanna, Ellanda Rima; Safitri, Erwina; Septiani, Baiq Dewi Sukma (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Stunting remains a major public health issue in Indonesia, with long-term impacts on children’s physical and cognitive development. Optimal nutrition during the first 8000 days of life from conception to early adulthood is critical for preventing stunting. Innovative and engaging educational strategies are essential to raise awareness in rural communities. Objective: The purpose of this service was to improve knowledge and awareness regarding nutrition during the first 8000 days of life as a strategy to prevent stunting through the use of the educational board game Monopoly NutriBoard in Harjomulyo Village. Method: This community service activity was implemented through interactive educational sessions involving adolescent and children in Forum Anak Desa (FAD) Harjomulyo. The Monopoly NutriBoard game was used as a participatory learning medium. Pre- and post-intervention questionnaires were administered to evaluate changes in participants’ knowledge and perceptions. Result: The educational intervention using Monopoly Nutriboard effectively increased participants’ understanding of the importance of nutrition in the first 8000 days of life. Participants demonstrated improved awareness of stunting risks and healthy nutrition practices. Engagement with the game facilitated interactive learning and community involvement. Conclusion: Monopoly NutriBoard proved to be an effective educational tool for promoting nutrition knowledge and stunting prevention awareness in a rural setting. Its interactive nature encourages community participation and can be scaled for broader use in public health education.